Stress corrosion cracking of high strength stainless steels for use as strand in prestressed marine environment concrete construction. Issue 11 (10th April 2015) - Fernandez, J.
<x xml:space="preserve">Abstract</x> Stainless steel reinforcement has an elevated chloride threshold and is an attractive alternative for prestressed concrete applications. However, due to the high strength requirements for prestressing strands, concern exists about the possibility of stress corrosion cracking (SCC). A possible candidate high strength alloy for use as prestressed strands in a Florida marine environment is UNS# S24000. Previous testing methods used on other stainless steel alloys were investigated to determine the best way to evaluate the UNS# S24000 as compared to other alloys. The alloys tested were a common austenitic stainless steel with high nickel content UNS # S31603, UNS# S24000, and a duplex stainless steel with high chromium and an additional constituent, molybdenum UNS# S32205. Prior work on high strength stainless steels have tested various alloys of austenitic steels or austenitic and duplex steels, but did not include UNS# S24000. The alloys examined were evaluated at various temperatures in magnesium chloride solutions and in a simulated concrete pore water solution at 60 °C, followed by an anodic polarization regime as an alternative test acceleration method. The results suggest that duplex high‐strength stainless UNS# S32205 performed overall better than the other two alloys. The UNS# S24000 still performed well in simulated concrete pore water and chloride solution tests, and performed better that UNS#S32205 at high temperatures in the tests in the magnesium chloride solution.